2009
DOI: 10.1590/s0037-86822009000500016
|View full text |Cite
|
Sign up to set email alerts
|

Formigas (Hymenoptera: Formicidae) como vetores de bactérias em dois hospitais do município de Divinópolis, Estado de Minas Gerais

Abstract: Entre os Artrópodes, os insetos sociais, e particularmente as formigas, estão entre os animais que melhor se adaptaram ao ambiente urbano, apresentando uma maior diversidade nas regiões tropicais. Estima-se que existam cerca de 18.000 espécies de formigas em todo o mundo, sendo no Brasil já catalogadas mais de 2.000 espécies. Poucas espécies de formigas são importantes por causarem problemas ao homem, sendo que apenas 1% são consideradas pragas e menos de 50 espécies estão adaptadas ao ambiente urbano 4 .Por a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 9 publications
1
8
0
7
Order By: Relevance
“…The genera identified in the present study have been described in previous investigations on the presence of ants in hospital environments in Brazil [5,6,14,32]. The studies cited revealed that ant diversity in Brazilian hospitals is consistently high [33].…”
Section: Resultssupporting
confidence: 72%
“…The genera identified in the present study have been described in previous investigations on the presence of ants in hospital environments in Brazil [5,6,14,32]. The studies cited revealed that ant diversity in Brazilian hospitals is consistently high [33].…”
Section: Resultssupporting
confidence: 72%
“…To date, there have been no reports on the association of fungi with the genus Odontomachus, although the association of these ants with bacteria has been studied (Caetano et al 2009, dos Santos et al 2009). The role of ants, including Odontomachus spp, as mechanical vectors of pathogenic bacteria within hospitals was recently demonstrated by dos Santos et al (2009), uncovering a public health problem because these bacteria can be directly associated with nosocomial infections.…”
Section: Resultsmentioning
confidence: 99%
“…The role of ants, including Odontomachus spp, as mechanical vectors of pathogenic bacteria within hospitals was recently demonstrated by dos Santos et al (2009), uncovering a public health problem because these bacteria can be directly associated with nosocomial infections. In another study, bacteria were found in the digestive tract of O. bauri, the same species of ant as investigated in the present study, suggesting the participation of these bacteria in the food digestion of this ant (Caetano et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…As formigas poderiam facilitar a sua instalação carreando os endósporos. Para Santos et al 14 , o conhecimento sobre a espécie, nicho e o modo de vida desses artrópodes podem ajudar na formulação de medidas profiláticas e de controle de infecções hospitalares, bem como o conhecimento sobre as bactérias que eles carreiam. Guilarde et al 15 constataram que 34,5% de letalidade, associada às infecções da corrente sanguínea, esta associado a bactérias oportunistas carreadas por formigas.…”
Section: Discussionunclassified